The first two mitochondrial genomes for the genus Ramaria reveal mitochondrial genome evolution of Ramaria and phylogeny of Basidiomycota - Qiang Li; Lijiao Li; Ting Zhang; Peng Xiang; Qian Wu; Wenying Tu; Zhijie Bao; Liang Zou; Cheng Chen (IMA Fungus, 2022)
Abstract In the present study, we assembled and analyzed the mitogenomes of two Ramaria species. The assembled mitogenomes of Ramaria cfr. rubripermanens and R. rubella were circularized, with sizes of 126,497 bp and 143,271 bp, respectively. Comparative mitogenome analysis showed that intron region contributed the most (contribution rate, 43.74%) to the size variations of Ramaria mitogenomes. The genetic contents, gene length, tRNAs, and codon usages of the two Ramaria mitogenomes varied greatly. In addition, the evolutionary rates of different core protein coding genes (PCGs) in Phallomycetidae mitogenomes varied. We detected large-scale gene rearrangements between Phallomycetidae mitogenomes, including gene displacement and tRNA doubling. A total of 4499 bp and 7746 bp aligned fragments were detected between the mitochondrial and nuclear genomes of R. cfr. rubripermanens and R. rubella, respectively, indicating possible gene transferring events. We further found frequent intron loss/gain and potential intron transfer events in Phallomycetidae mitogenomes during the evolution, and the mitogenomes of R. rubella contained a novel intron P44. Phylogenetic analyses using both Bayesian inference (BI) and Maximum Likelihood (ML) methods based on a combined mitochondrial gene dataset obtained an identical and well-supported phylogenetic tree for Basidiomycota, wherein R. cfr. rubripermanens and Turbinellus floccosus are sister species. This study served as the first report on mitogenomes from the genus Ramaria, which provides a basis for understanding the evolution, genetics, and taxonomy of this important fungal group.